SWOT Analysis to Determine Competitive Strategy at PT. Oceanias Timber Products - Jasmine Salsabilla, Putri (Siber Journal of Transportation and Logistics, 2023)
This research aims to determine a competitive strategy for PT. Oceania Wood Products through SWOT analysis. This analysis identifies company strengths such as high product quality and an extensive distribution network, as well as weaknesses such as dependence on imported raw materials and high production costs. Based on the results of the SWOT analysis, the recommended competitive strategies include: environmentally friendly product diversification, optimizing production cost efficiency, expanding into international markets, and partnership building strategies. Implementation of this strategy is expected to strengthen PT's market position. Oceania Wood Products, increase competitiveness, and achieve sustainable growth.